The Effect of Yoga on Pain and Quality of Life in Primary Dysmenorrhea: A Cross Sectional Survey : Effect of Yoga On Primary Dysmenorrhea - Salman, Muhammad; Umar, Muhammad; Shahid, Hamza; Haq, Kiran; Asif, Somiya; Talha, Muhammad (Pakistan Journal of Health Sciences, 2022)
Dysmenorrhea is a painful syndrome that accompanies the menstrual cycles. Objectives: The main objective of this research was to determine the effects of yoga exercises on pain and quality of life in female undergraduate students suffering from primary dysmenorrhea. Methods: After taking approval from Ethical review committee of Rawal Institute of Health Sciences, an observation type of cross-section survey was conducted in 470 young undergraduate female students of age between 17-26, suffering from primary dysmenorrhea. By non-probability sampling participants were divided into two groups. Group-1 was of those females who had active lifestyle and doing yoga exercises and group-2 were of those who had sedentary lifestyle and didn’t do any kind of exercise. To measure the outcome variables, EQ-5D-5L questionnaire was used to measure QoL & NPRS to measure pain. Data were taken at baseline and after 12th week. Wilcoxon rank test was used for within group analysis and Mann Whitney U test was used to compare mean between groups. Data was analyzed in SPSS software version 21 along with Microsoft Excel 2019. Results: 21.16+2.66 &22.27+2.53 was the Mean+SD of age of group-1 & group-2 respectively. Between groups analysis revealed that p-value for NPRS was <0.05 but was >0.05 in quality of life. Conclusion: Yoga exercises are safer and easiest way to manage pain of primary dysmenorrhea in undergraduate females without any drug use.